Australian Unions: An Industrial Relations Perspective - Benson, John (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "Australian Unions: An Industrial Relations Perspective," by Bill Ford and David Plowman.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z